Beta-blockers for heart failure - Cleland, John GF (Cochrane Database Syst Rev, 2000)
This is the protocol for a review and there is no abstract. The objectives are as follows: Our objective is to appraise the effectiveness of beta blockers in patients with heart failure. Our protocol defined main outcome is all cause mortality. The specific a priori defined aims are to examine: the effectiveness of beta blockers in all trials of patients with heart failure, and examine the importance of the presence or absence of ischaemic cardiomyopathy in patients included in trials and vasodilator properties of beta blocking agents used. We will also examine the predictive value of left ventricular function, age, use of angiotensin converting enzyme inhibitors and New York Heart Association Class (NYHA), and the rate of discontinuation of therapy due to treatment. There are a number of important ongoing trials for which data will become available in the next few years. Thus a systematic review which may be updated regularly is required to provide an up to date synthesis of the available data in this increasingly important area.